2021
DOI: 10.3390/biomedicines9111554
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Nanoparticles for the Detection and Imaging of Ovarian Cancers

Abstract: Ovarian cancer remains as one of the most lethal gynecological cancers to date, with major challenges associated with screening, diagnosis and treatment of the disease and an urgent need for new technologies that can meet these challenges. Nanomaterials provide new opportunities in diagnosis and therapeutic management of many different types of cancers. In this review, we highlight recent promising developments of nanoparticles designed specifically for the detection or imaging of ovarian cancer that have reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 170 publications
(243 reference statements)
0
3
0
Order By: Relevance
“…Mouse ascites was used as a rich cellcontaining biological fluid distinct from blood and plasma, yet highly relevant in the study of tumor immunology. 40 These results indicate that the nanoparticles should be stable in biological conditions, provided proper resuspension prior to use.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Mouse ascites was used as a rich cellcontaining biological fluid distinct from blood and plasma, yet highly relevant in the study of tumor immunology. 40 These results indicate that the nanoparticles should be stable in biological conditions, provided proper resuspension prior to use.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…59 This finding in combination with our own indicates that the various organosilica nanoparticle formulations can significantly affect immune cell interactions. In a different study by Karlson et al,40 and 500 nm glycine coated polystyrene nanoparticles were both found to generate negligible immune response in BM cultures, hypothesized to be due to a lack of oxidative stress in the cells as they also found negligible increases to redox-sensitive extracellular signal-regulating kinase pathways. 4 Cytokine release in TiO 2 nanoparticles was found to be size dependent in cell line studies, with 1000 nm particles generating significantly higher TNF-α response than 40 nm particles across a wide range of concentrations.…”
Section: ■ Nanoparticle Association With Bone Marrow Derived Cell Cul...mentioning
confidence: 94%
“…Nanotechnology thus provides novel molecular agents that could enable OC diagnosis at initial stages and allow continuous monitoring during treatment (Rajitha et al, 2021). By serving as contrast agents, molecular imaging agents and intraoperative aids, novel nanomaterials improve traditional clinical methods by recognizing OC early and precisely positioning it (Henderson et al, 2021). For instance, Williams et al reported a optically responsive carbon nanotube to detect the OC biomarker HE4 in vivo (Williams et al, 2018).…”
mentioning
confidence: 99%